Rent-seeking behaviour and ẓulm (injustice/exploitation) beyond ribā-interest equation - Mohammad O. Farooq (ISRA International Journal of Islamic Finance, 2019)
Purpose: The purpose of this paper is to explore the concept of rent-seeking behaviour and rentier state in the context of ẓulm (injustice and exploitation), which is one of the key concerns in Islam in general and Islamic economics and finance in particular. Design/methodology/approach - As a conceptual paper, it draws on the literature of rent-seeking as part of public choice theory and examines the potential vulnerabilities as well as existence of rent-seeking in Muslim-majority countries, where Islamic finance industry primarily operates. Findings - The paper identifies several areas where both actual and potential rent-seeking exists. Research limitations/implications - The paper is conceptual. Based on the analysis presented here further studies can be undertaken to determine the scope of rent-seeking and their impact in Muslimmajority societies. Practical implications - Incorporating rent-seeking in the theoretical and conceptual framework of Islamic economics and finance can enhance understanding about ẓulm and its ubiquitous presence, as Islam has a firm stance to aspire to have a ẓulm-free society. Social implications - Understanding rent-seeking behaviour can help appreciate why corruption, inequality and poverty are so entrenched, and why limiting the discourse to riba (interest) ignores the broader scope of injustice and exploitation. Originality/value - This might be the first focused paper that conceptually deals with rent-seeking behaviour, connecting the discourse about riba-interest equation.
Keywords: 330; Rentier economy; Rent-seeking culture; Unearned gain; Economic exploitation; Ẓulm-free society